Analisa Pengaruh Cost Leadership, Differentation Strategy dan Market Orientation Terhadap Kinerja Perusahaan - Lily Purwianti (Program Sarjana Manajemen Universitas Internasional Batam, 2019)
The main purposes of this study is to analyze the relationship of cost leadership, differentiation strategy, market orientation and organization performance. The research sample are souvenirs shop in Batam City. Multiple regression analysis to test the hypothesis. The results of this study are information about cost leadership, differentiation strategies, market orientation towards company performance. The results showed that cost leadership, differentiation strategy, market orientation has significant efect on organization performance.